The post carbon reader managing the 21st century's sustainability crises - Heinberg, Richard; Lerch, Daniel (Healdsburg, California, USA Watershed Media, 2010)
"In the 20th century, cheap and abundant energy brought previously unimaginable advances in health, wealth, and technology, and fed an explosion in population and consumption. But this growth came at an incredible cost. Climate change, peak oil, freshwater depletion, species extinction, and a host of economic and social problems now challenge us as never before. The Post Carbon Reader features articles by some of the world's most provocative thinkers on the key drivers shaping this new century, from renewable energy and urban agriculture to social justice and systems resilience. This unprecedented collection takes a hard-nosed look at the interconnected threats of our global sustainability quandary--as well as the most promising responses. The Post Carbon Reader is a valuable resource for policymakers, college classrooms, and concerned citizens."--Publisher's description.
Part I. Foundation concepts : ch. 1. Beyond the limits to growth / Richard Heinberg -- ch. 2. What is sustainability? / Richard Heinberg -- ch. 3. Thinking "resilience" / William E. Rees -- Part II. Climate : ch. 4. A new world / Bill McKibben -- ch. 5. The international response to climate change / Richard Douthwaite -- ch. 6. The ecological deficit : creating a new political framework / David Orr -- Part III. Water : ch. 7. Water : adapting to a new normal / Sandra Postel -- Part IV. Biodiversity : ch. 8. Peak nature? / Stephanie Mills -- Part V. Food : ch. 9. Getting fossil fuels off the plate / Michael Bomford -- ch. 10. Tackling the oldest environmental problem : agriculture and its impact on soil / Wes Jackson -- ch. 11. Growing community food systems / Erika Allen -- Part VI. Population : ch. 12. Population : the multiplier of everything else / William N. Ryerson -- Part VII. Culture and behavior : ch. 13. Dangerously addictive : why we are biologically ill-suited to the riches of modern America / Peter C. Whybrow -- ch. 14. Remapping relationships : humans in nature / Gloria Flora -- ch. 15. The human nature of unsustainability / William E. Rees -- Part VIII. Energy : ch. 16. Making sense of peak oil and energy uncertainty / Daniel Lerch -- ch. 17. Hydrocarbons in North America / J. David Hughes -- ch. 18. Nine challenges of alternative energy / David Fridley -- ch. 19. Peak oil and the great recession / Tom Whipple -- Part IX. Economy : ch. 20. Ecological economics / Joshua Farley -- ch. 21. Money and energy / Richard Douthwaite -- ch. 22. The competitiveness of local living economies / Michael H. Shuman -- Part X. Cities, towns, and suburbs : ch. 23. The death of sprawl: designing urban resilience for the twenty-first-century resource and climate crises / Warren Karlenzig -- ch. 24. Smart decline in post-carbon cities : the Buffalo Commons meets Buffalo, New York / Deborah E. Popper and Frank J. Popper -- ch. 25. Toward zero-carbon buildings / Hillary Brown -- ch. 26. Local government in a time of peak oil and climate change / John Kaufmann -- Part XI. Transportation : ch. 27. Transportation in the post-carbon world / Richard Gilbert and Anthony Perl -- Part XII. Waste : ch. 28. Climate change, peak oil, and the end of waste / Bill Sheehan and Helen Spiegelman -- Part XIII. Health : ch. 29. Human health and well-being in an era of energy scarcity and climate change / Cindy L. Parker and Brian S. Schwartz -- Part XIV. Education : ch. 30. Smart by nature : schooling for sustainability / Michael K. Stone and Zenobia Barlow -- ch. 31. Community colleges : a vital resource for education in the post-carbon era / Nancy Lee Wood -- Part XV. Building resilience -- ch. 32. Personal preparation / Chris Martenson -- ch. 33. What can communities do? / Rob Hopkins -- Part XVI. Call to action : ch. 34. What now?: the path forward begins with one step / Asher Miller.
Includes bibliographical references and index.
Keywords: Energy policy -- Environmental aspects; Climatic changes -- Government policy; Economic development -- Environmental aspects; Sustainable development; Human ecology; Environmental economics; Environmental protection; Environmental degradation; Hubbert peak theory; Environmental justice; Energy development; Renewable energy sources